The Tale "Place for the Dragon" by Yuriy Vynnychuk in the 8th grade of the secondary school (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In modern curriculum with Ukrainian literature introduced for study in 8 class story-tale of  Yuri Vynnychuk «The place for the dragon». The proposed article provides guidelines for its consistent consideration, interpreting and commenting teacher. Made focus on the urgency of the work, originality literary hoax in it – the image of a dragon Gregory, who, by tradition, is not the embodiment of evil, and makes self-sacrifice for the future happiness of mankind.
Keywords: story-tale; literary context; literary hoax; implications